Risk and resilient architectural practices in informal settlements – the role of NGOs. Issue 4 (29th August 2019) - Martins, A. Nuno; Rocha, Aline
Abstract : Purpose: The purpose of this paper is to understand the role played by small-size non-governmental organisations (NGOs) in slum upgrading, building and incremental housing processes in Brazil and Guinea-Bissau, focusing, in particular, on actions to reduce vulnerabilities and enhance community resilience. Design/methodology/approach: The research method relied on literature review and fieldwork. It included surveys, activities with the communities, interviews and questionnaires. The data collected were subject to cross-disciplinary and comparative analysis. Findings: The paper analyses the innovative methods and solutions used by NGOs in informal settlement upgrading and housing improvement works related to disaster risk reduction, namely, community mapping and design, and show how they end up building community resilience. Research limitations/implications: Grasping the impacts of NGOs' work whether in slums of Brazil or Africa requires staying with communities for a significant amount of time. However, those stays raise many practical problems regarding security, health and related costs. Originality/value: The existing literature misses to address from a comparative perspective, the methods used by social workers and designers teams in slums. This paper aims at filling this gap in slum studies. Its originality and value rely on the particular experience of the authors, who were personally involved in the NGOs actions and could deepen the connections between vulnerabilities, risk and successful aid-self-help practices.